Thermal enhancement of rectangular channels using hook-shaped fins and dimples. (25th November 2022) - Khaled, Omar; Swift, John; Kempers, Roger
Highlights: Hook-shaped fins and dimples were used to enhance the convection heat transfer. Hook geometries and clearances were tested in air at Re from 4000 to 20000. Hooks increased Nu by 4 and friction factor by up to 12 times that of a flat plate. Increasing the tip clearance reduced the friction factor and Nu. Interfin spacing and height exhibited a minimal effect on Nu at high clearance. Correlations were developed for Nu and friction factor. Abstract: A common technique for enhancing convective heat transfer from a surface is to add extended surfaces (fins); the size and shape of these fins play a crucial role in their performance. Many studies have investigated ways to leverage novel manufacturing techniques to create different fin shapes to improve thermal-fluidic performance. A skiving process which creates a unique array of hook-shaped raised features (hooks) and cavities (dimples) on metal surfaces (GRIPMetal) has been developed. The present work experimentally characterizes the thermal and hydraulic performance of rectangular channels with an array of these hooks and dimples on their opposing major surfaces and compares these channels to channels with bare surfaces and other fin structures. Three different hook sizes with nominal hook heights, h, of 1 mm, 1.5 mm and 2.25 mm and different inter-fin spacings were investigated. The effect of tip clearance above the hooks, C, was investigated for clearances of h, 2  h, 4  h, 6.5  h . Results were obtained for air at Reynolds numbers from 4, 000 to 20, 000. The overall Nusselt numbers and friction factors were calculated, and empirical correlations were developed through nonlinear multivariable regression. The array of hooks increased the Nusselt number, Nuh, up to a factor of 4 depending on Re, while the maximum increase in the friction factor, fh, was 12 at the highest Re . Generally, increasing the tip clearance decreased the friction factor and Nusselt number for the channel. Hook height and inter-fin spacings have no effect on thermal performance at high tip clearances (above C  = 4  h ), while the hydraulic performance shows a recognizable dependency.